Digital Competence for Teachers and Students in a Legal and University Context - Merchán Murillo , Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Today both students and teachers need to obtain digital skills. Focusing on the Degree in Law, we are facing the challenge of adapting new techniques to correctly, ethically and effectively train all its members. In this sense, it is about analyzing and trying to address the use of technology for learning and its underlying complexity, as well as the teaching process and the need to support students.